2013
DOI: 10.1158/1078-0432.ccr-13-1326
|View full text |Cite
|
Sign up to set email alerts
|

miR-200b and miR-200c as Prognostic Factors and Mediators of Gastric Cancer Cell Progression

Abstract: Purpose: The purpose of this study was to investigate the clinicopathologic significance and potential role of miR-200b and miR-200c

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 37 publications
5
124
1
1
Order By: Relevance
“…We have also observed an inverse correlation between the expression levels of miR200c and that of JNK2, ABCB1, and MMP-2/-9, which predicts the treatment outcome in patients with locally advanced colorectal cancer administrated with standard postsurgery chemotherapy regime (FOLFOX or CapeOX). We further demonstrated that the decreased levels of miR200c correlated with the clinical data of patients responding poorly to chemotherapy (42). It indicates that decreased miR200c expression may be the main mechanism that positively regulates P-gp and MMP-2/-9 expression in MDR colorectal cancer.…”
Section: Discussionmentioning
confidence: 59%
“…We have also observed an inverse correlation between the expression levels of miR200c and that of JNK2, ABCB1, and MMP-2/-9, which predicts the treatment outcome in patients with locally advanced colorectal cancer administrated with standard postsurgery chemotherapy regime (FOLFOX or CapeOX). We further demonstrated that the decreased levels of miR200c correlated with the clinical data of patients responding poorly to chemotherapy (42). It indicates that decreased miR200c expression may be the main mechanism that positively regulates P-gp and MMP-2/-9 expression in MDR colorectal cancer.…”
Section: Discussionmentioning
confidence: 59%
“…miRNAs play a vital role in many crucial cellular processes, including apoptosis, differentiation, invasion, and proliferation (32)(33)(34). The abnormal expression of miRNA has been reported in many cancers, including breast (35), gastric (36), colorectal (37), and liver cancers (38), as well as leukemia (39) and lymphoma (40). miR-124 has been described as a brain-specific miRNA in mammals, and may play a role in defining and maintaining neuron-specific characteristics (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…miR-200c is a member of the miR-200 family, which was previously shown to inhibit epithelialto-mesenchymal transition (EMT) by targeting the transcriptional repressor of cadherin 1(CDH1), zinc finger E-box binding homeobox 1 (ZEB1), and survival of motor neuron protein interacting protein 1(SIP1); this suggests that these miRNAs could prevent tumor progression by negatively regulating ZEB transcriptional repressors and consequently maintaining E-cadherin junctions and preventing EMT (Bracken et al, 2008;Gregory et al, 2008;Korpal et al, 2008;Park et al, 2008). Upregulation of miR-200c had been found in several cancers, including ovarian cancer (Iorio et al, 2007;Bendoraite et al, 2010), cervical cancer , bile duct cancer (Meng et al, 2006), nasopharyngeal carcinoma (Zhang et al, 2010), lung cancer (Liu et al, 2012), and colorectal cancer (Zhang et al, 2013;Cristobal et al, 2014), as well as GC (Tang et al, 2013;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that human serum contains miRNAs and that their expression patterns can potentially be used as clinically diagnostic and prognostic biomarkers of various cancers (Cortez et al, 2009(Cortez et al, , 2012. ) is a member of the miR-200 family, which is overexpressed in several cancers, including ovarian cancer (Iorio et al, 2007;Bendoraite et al, 2010), cervical cancer , bile duct cancer (Meng et al, 2006), nasopharyngeal carcinoma (Zhang et al, 2010), lung cancer (Liu et al, 2012), colorectal cancer (Zhang et al, 2013;Cristobal et al, 2014), and GC as well (Tang et al, 2013;Song et al, 2014). Valladares-Ayerbes et al (2012) found that the miR-200c blood expression levels in GC patients were significantly higher than in normal controls (P = 0.018) and that it has the potential to be a predictor of progression and survival.…”
Section: Introductionmentioning
confidence: 99%